Diversity of Tuber Crops and Arbuscular Mycorrhizae Fungi (Amf) Under Community Forest Stand in South Sulawesi - Retno Prayudyaningsih; Nursyamsi (Jurnal Penelitian Kehutanan Wallacea, 2015)
Implementation of agroforestry system in community forest that incorporate local species Vitex cofassus (bitti), Toona sinensis (suren), Tectona grandis (teak) and Aleurites moluccana (candlenut) with seasonal crops such as tuber crops would create opportunities for local people to improve the economic and food security. Tuber crops as the understory could be expected to reduce the rate of soil erosion and expand habitat of beneficia soil microorganisms such as arbuscular mycorrhizal fungi (AMF). The research aims to determine the diversity of tuber crops and AMF in the rhizosphere of tuber crops grown under community forest stands of bitti, suren, teak and candlelnut in South Sulawesi. Results showed that (1) there are 12 kinds of tuber crops that grow under community forest stands in which the 7 types are as alternative food sources, (2) Amorphophallus campanulatus (iles-iles/suweg) and Xanthosoma violaceum (kimpul) are species of tuber crops that is found growing under all of the commnunity forest stands, (3) all kinds of tuber crops that grow under the community forest stand associated with AMF, in which there are 3 AMF genus i.e Glomus sp. Acaulospora sp. and Gigaspora sp.with low spore density.